INFORMATIONAL RESOURCES ON POTATO GERMPLASM COLLECTIONS - D. A. Afonnikov; I. V. Totsky; Z. Stasevski (Вавиловский журнал генетики и селекции)
The potato (Solanum tuberosum L.) is one of the most important food crops, the advantage of which is the ability to give a high yield in a wide range of agroecosystems, high specific production of dry weight per unit of cultivated area. Nowadays potato is considered a source of vitamins, minerals, dietary fiber and other nutrients. Potato cultivars are characterized by low genetic diversity, which reduces their potential to produce varieties with improved properties. Wild potato relatives retain a high degree of genetic diversity, which can be used to find the superior alleles and for their further transfer to cultural genotypes. To this end, there is an intense development of potato gene banks, with the help of the information technology to access the data. The present review is devoted to global information resources in potato. It describes the most relevant information portals and databases of genetic resources for potatoes. Analysis of information in the Internet shows that the main information resources on potato collections are concentrated in the United States and Europe. Information portals provide a wide variety of information useful to producers, consumers and breeders. On such portals, there is an intensive information support of the latest technologies in the field of potato growing and breeding. An interesting direction is the provision of services to determine the DNA prints (markers) of potato varieties, involvement of potato growers in the process of operational monitoring of diseases and pests of potatoes. Integration of data on potato collections plays an important role at the present stage. In line with this, European collections and databases are being developed. However, despite the existence of pan-European potato collection, national collections are still given support. An important collection-related trend in recent years has been inclusion of samples with a large number (more than a hundred) characteristics, which are evaluated by constantly testing varieties within the framework of foreign state breeding programs. As a result of access to such information, the breeder can effectively plan an experiment with the purpose of directed selection for key features of plants. These trends confirm the effectiveness of the use of the latest technologies (including information) in the maintenance and dissemination of potato genetic resources.